Correlation between GNSS-TEC and eruption magnitude supports the use of ionospheric sensing to complement volcanic hazard assessment - Manta, Fabio (2021)
Despite the global threat posed by large-scale eruptions to communities, to the climate, and to the consequent impacts on the world economy, many active volcanoes still lack of adequate ground-based instrumentation. Satellite-based remote sensing has been used to complement volcano monitoring and risk assessment for volcanic ash, but this technique is often limited by weather conditions. In this work, we explore the ionospheric total electron content (TEC) perturbations measured by GNSS to provide additional information and complement conventional monitoring systems. To this end, we measure the GNSS TEC perturbation associated with the acoustic-gravity waves generated by 22 volcanic explosions. We introduce a new metric—the Ionospheric Volcanic Power Index (IVPI)—to quantify the energy transferred to the ionosphere by volcanic explosions. We evaluate the IVPI against several well-established metrics from seismic and infrasonic volcano monitoring as well as satellite remote sensing. Our results show that the IVPI successfully correlates with the Volcanic Explosivity Index (VEI) for events larger than VEI 2. Moreover, the IVPI shows strong correlation with both the acoustic source power and the ash plume height, from which depends the style of volcanic activity. Moderate correlation between IVPI and peak ground velocity (PGV) requires further study in order to evaluate the role of different parameters (seismic magnitude, attenuation, style of faulting, crustal structure, etc.). Our results suggest that ionospheric monitoring by GNSS TEC can help to characterize volcanic eruptions, opening new exciting avenues for continuous volcano monitoring and warning systems by remote sensing.